2009
DOI: 10.1111/j.1600-0706.2008.16849.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance frequency and functional identity mediate ecosystem processes in prairie streams

Abstract: A major consequence of climate change will be the alteration of precipitation patterns and concomitant changes in the flood frequencies in streams. Species losses or introductions will accompany these changes, which necessitates understanding the interactions between altered disturbance regimes and consumer functional identity to predict dynamics of streams. We used experimental mesocosms and field enclosures to test the interactive effects of flood frequency and two fishes from distinct consumer groups (benth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 63 publications
1
26
1
Order By: Relevance
“…Thus, drying may intensify consumer effects only in the absence of severe summer spates. In contrast to our results (weaker consumer effects following spates), Bertrand et al (2009) found grazing and water-column consumers such as southern redbelly dace (Phoxinus erythrogaster) and red shiners (Cyprinella lutrensis) altered recovery of periphyton communities in mesocosms following a simulated spate. Additionally, time since disturbance altered or reversed consumer effects.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Thus, drying may intensify consumer effects only in the absence of severe summer spates. In contrast to our results (weaker consumer effects following spates), Bertrand et al (2009) found grazing and water-column consumers such as southern redbelly dace (Phoxinus erythrogaster) and red shiners (Cyprinella lutrensis) altered recovery of periphyton communities in mesocosms following a simulated spate. Additionally, time since disturbance altered or reversed consumer effects.…”
Section: Discussioncontrasting
confidence: 86%
“…Additionally, time since disturbance altered or reversed consumer effects. Consumers did not alter recovery in stream enclosures, perhaps because enclosures were not large enough for consumers to affect nutrient cycling (Bertrand et al, 2009). Additional long-term studies are needed to assess how different environmental disturbances like spates and drying interact to influence ecological interactions in streams (e.g., Power et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Productivity and nutrient uptake rates mimicked algal biomass, and following an algal transition due to senescing filaments, algal structure and April 2010 1055 CONSUMERS ALTER DROUGHT RECOVERY function in control and exclosure cages were similar (i.e., there was an eventual weakening of macroconsumer impact). Algal recovery in cages open to macroconsumers was more similar to typical algal recovery in Kings Creek (e.g., Dodds et al 1996, Bertrand et al 2009). Therefore, a surprising result was a convergence of treatment trajectories in late succession with benthic communities reaching a similar state regardless of macroconsumer presence.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, transient effects of consumers are a vital component of these ecosystems, making them a good model system to evaluate the relationships between consumers and their temporal patterns of colonization and recovery. The recovery of structural and functional properties of producers in intermittent streams have been studied in some streams (e.g., Fisher et al 1982, Dodds et al 1996, Boulton 2003, Biggs et al 2005, but the role of consumers influencing recovery following disturbance in streams is not as well documented (but see Gelwick and Matthews 1992, Pringle and Hamazaki 1997, Bertrand et al 2009). Consumer effects in streams are generally strong during equilibrium states (Feminella and Hawkins 1995, Steinman 1996, Hillebrand 2002, but disturbances have the potential to change these interactions by altering community structure and producer growth rates (Whittaker 1965, Connell 1978, Huston 1979, Resh et al 1988, Biggs et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Although these results are limited by the number of factors we could test, the fact that newC 18:3x3/PUFA was both highly plausible and found to be the single best model to explain variation in newC ia15:0/PUFA indicates that the relative activity of green algae can be important in regulating direct algal-bacterial C exchange in these biofilms. Given the disturbance regime of streams in this region (Lohman et al, 1991) and the interactive effects of nutrients and biofilm development observed in other streams (Bertrand et al, 2009), it is likely that the negative relationship between green algal activity and algal-bacterial C exchange observed here is attributed to variation in biofilm development. Specifically, the composition of active phototrophs, such as relative activity of green algae, may be regulated by the extent of biofilm development in these streams (Power et al, 2008).…”
Section: Discussionmentioning
confidence: 96%